Iodine status and thyroid function among Spanish schoolchildren aged 6–7 years: the Tirokid study. Issue 9 (10th March 2016) - Vila, L.; Donnay, S.; Arena, J.; Arrizabalaga, J. J.; Pineda, J.; Garcia-Fuentes, E.; García-Rey, C.; Marín, J. L.; Serra-Prat, M.; Velasco, I.; López-Guzmán, A.; Luengo, L. M.; et al.
Abstract: I deficiency is still a worldwide public health problem, with children being especially vulnerable. No nationwide study had been conducted to assess the I status of Spanish children, and thus an observational, multicentre and cross-sectional study was conducted in Spain to assess the I status and thyroid function in schoolchildren aged 6–7 years. The median urinary I (UI) and thyroid-stimulating hormone (TSH) levels in whole blood were used to assess the I status and thyroid function, respectively. A FFQ was used to determine the consumption of I-rich foods. A total of 1981 schoolchildren (52 % male) were included. The median UI was 173 μg/l, and 17·9 % of children showed UI<100 μg/l. The median UI was higher in males (180·8 v. 153·6 μg/l; P <0·001). Iodised salt (IS) intake at home was 69·8 %. IS consumption and intakes of ≥2 glasses of milk or 1 cup of yogurt/d were associated with significantly higher median UI. Median TSH was 0·90 mU/l and was higher in females (0·98 v. 0·83; P <0·001). In total, 0·5 % of children had known hypothyroidism (derived from the questionnaire) and 7·6 % had TSH levels above reference values. Median TSH was higher in schoolchildren with family history of hypothyroidism. I intake was adequate in Spanish schoolchildren. However, no correlation was found between TSH and median UI in any geographical area. The prevalence of TSH above reference values was high and its association with thyroid autoimmunity should be determined. Further assessment of thyroid autoimmunity in Spanish schoolchildren is desirable.